Credit growth and moral hazard: An empirical study of the causes of credit expansion by the Finnish local banks in 1986-1990 - Vesa Vihriälä (Bank of Finland, 1996)
The paper examines the determination of bank lending during the Finnish credit boom of 1986-1990 with the data of 483 savings and cooperative banks.A particular objective is to establish whether bank behaviour is consistent with what is called moral hazard hypothesis, according to which banks expanded risky lending in part to benefit from underpricing of bank liabilities and/or anticipated bank support policies, which would reward capital insufficiency.The results strongly support the moral hazard hypothesis.Growth of lending was, ceteris paribus, negatively associated with bank capital and positively associated with bank costs.Also the behaviour of subordinated debt is consistent with the moral hazard hypothesis.The findings suggest that the cause of such behaviour was underpriced non-deposit liabilities rather than underpriced deposit insurance or anticipation at perverse bank policies.The perverse behaviour was much stronger among the savings banks than among the cooperative banks.According to calculations based on the estimation results, the growth rate of savings bank lending had been 1/3 smaller than the actual growth rate in 1986-1990 in the absence of moral hazard.In the case of the cooperative banks the estimated moral hazard effect is less than l/10 of the growth rate.Given the clear positive association of the rate of growth of lending during the boom period and the amount of non-performing assets later during the banking crisis, the disproportionary losses of the savings bank group are - in the light of this analysis - largely due to moral hazard.Consequently also most of the government expenditure on bank support appears to be caused by distorted incentives.
URN:NBN:fi:bof-20140807204
Keywords: 330; bank lending; moral hazard; deposit insurance; creditor protection; bank support